2022
DOI: 10.1001/jamacardio.2022.0043
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Outcomes of Type 2 Myocardial Infarction

Abstract: IMPORTANCEIn contrast to type 1 myocardial infarction (T1MI) caused by atherothrombosis, characteristics and outcomes of type 2 myocardial infarction (T2MI) caused by supply-demand mismatch are incompletely understood.OBJECTIVE To explore the characteristics and outcomes of patients with T2MI compared with those with T1MI. DESIGN, SETTING, AND PARTICIPANTSIn a prospective, international, multicenter cohort study including 12 emergency departments (EDs) in 5 European countries, unselected patients presenting wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 26 publications
(82 reference statements)
2
14
1
1
Order By: Relevance
“…Several conditions are associated with T2AMI, however there is very little data specifying their prevalence. In our analysis we found SMuRF and SMuRF-less patients had similar secondary diagnoses, with respiratory disorders most prevalent, followed by cardiovascular and renal disorders which was in consistent with other studies [9,22,23]. This is important as the difference in the T2AMI outcomes cannot be associated with the underlying secondary diagnosis, but with the non-accountable characteristics of the population with a common endpoint of myocardial injury.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Several conditions are associated with T2AMI, however there is very little data specifying their prevalence. In our analysis we found SMuRF and SMuRF-less patients had similar secondary diagnoses, with respiratory disorders most prevalent, followed by cardiovascular and renal disorders which was in consistent with other studies [9,22,23]. This is important as the difference in the T2AMI outcomes cannot be associated with the underlying secondary diagnosis, but with the non-accountable characteristics of the population with a common endpoint of myocardial injury.…”
Section: Discussionsupporting
confidence: 90%
“…The SMuRF-less cohort likely include those with missed standard modifiable risk factors (which may have poor prognostic impact in a causal manner). They may include patients with atypical risk factors such as liver disease or cancer associated with worse prognosis, as shown in the present study and several others [3,9,[21][22][23], but observed not to be an explanation in the SWEDEHEART STEMI cohort. The third category of SMuRF-less AMI individuals particularly relevant to those with demonstrated atherosclerosis and vascular dysfunction, are those with true heightened susceptibility to these processes in the absence of risk factors.…”
Section: Discussioncontrasting
confidence: 52%
“…Future studies should observe the differences in mortality between patients admitted to rural and urban hospitals after discharge, as the urban-rural disparity in quality of care could lead to worse medium- and long-term survival outcomes among patients. Third, we did not have sufficient information identifying the clinical type of AMI [ 19 ]. As patients admitted to rural hospitals were older, more likely to be female, we speculate that a higher percentage of patients were Type 2 AMI in rural hospitals [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Third, we did not have sufficient information identifying the clinical type of AMI [ 19 ]. As patients admitted to rural hospitals were older, more likely to be female, we speculate that a higher percentage of patients were Type 2 AMI in rural hospitals [ 19 , 20 ]. Since indications to PCI and fibrinolysis were different according to type of MI, percentage of type 2 patients could potentially influence our results.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies describing the characteristics of patients with T2MI agree that they tend to be older, female, and have more chronic comorbidities. [2][3][4][5][6][7] However, there tends to be a significant discrepancy in reported hospitalization and mortality trends, associated comorbidities, and outcomes. [2][3][4][5][6][7][8] In the present study, we used the most recent data available from the NIS database (January 2018 to December 2019) to compare patients admitted to the hospital with a diagnosis of T2MI with patients admitted with a diagnosis of type 1 MI (T1MI).…”
Section: Introductionmentioning
confidence: 99%